2014
DOI: 10.4103/2231-0738.132678
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status of critically ill neurosurgical patients and parameters predicting the outcome: An institutional observational study

Abstract: Backdrop: Nutritional status has been proven to affect surgical outcome in various studies worldwide. Accurate nutritional assessment tools can help the clinician in taking appropriate steps at the right time in order to improve the surgical outcome. This is especially relevant in neurosurgical cases because of the long hospital stay and high incidence of complications. In the present study we aim to find out the prevalence of severe malnutrition in the patients admitted to NICU and the correlation of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[ 21 ] Recent data from a neurosurgical ICU in India reported that 42% of their patients were severely malnourished and 36% were moderately malnourished as per the SGA evaluation. [ 22 ] In a similar study in 500 critically ill patients, 39.6% of patients were moderately malnourished, whereas only one patient was noted to have severe malnutrition as per the SGA. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Recent data from a neurosurgical ICU in India reported that 42% of their patients were severely malnourished and 36% were moderately malnourished as per the SGA evaluation. [ 22 ] In a similar study in 500 critically ill patients, 39.6% of patients were moderately malnourished, whereas only one patient was noted to have severe malnutrition as per the SGA. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In a study performed by Bandlish et al in a neurosurgical intensive care unit in India, 36% of 50 elective cases had moderate and 42% had severe malnutrition. 43 The overall mortality rate of these patients was 36%. 43 They assessed severe malnutrition as serum albumin < 3.5 mg/dL and serum transferrin < 150mg/dL which were significantly associated with higher mortality in their study.…”
Section: Effects Of Malnutrition In Patients In Intensive Care Unitmentioning
confidence: 93%
“…43 The overall mortality rate of these patients was 36%. 43 They assessed severe malnutrition as serum albumin < 3.5 mg/dL and serum transferrin < 150mg/dL which were significantly associated with higher mortality in their study. 43 In German hospitals, Pirlich et al found that approximately 25% of patients is malnourished.…”
Section: Effects Of Malnutrition In Patients In Intensive Care Unitmentioning
confidence: 93%
See 1 more Smart Citation